Compressive strength of ultrahigh performance concrete incorporating palm oil clinker as aggregate replacement at different elevated temperatures - Nur Raidah, Mohd Rejuhan (2019)
Ultra-high performance concrete (UHPC) is a construction material with excellent mechanical properties and good durability as compared to conventional concrete. Despite its outstanding properties, UHPC also has some limitations in terms availability of raw constituent materials. UHPC require large amount of coarse aggregate in the production of UHPC. Therefore, the incorporation of waste material namely palm oil clinker (POC) as aggregate replacement in UHPC is a promising solution to these arising problems. This idea also was inspired from the crucial environmental issues that resulting from the disposal of palm oil waste. It not only minimize the degradation, but it also guides to sustainable development by ensuring the conservation of natural sources. Eventhough UHPC has impressive properties and strength, UHPC are having big challenge with fire and high temperature. In this study, the possibility of using POC as aggregate replacement was investigated. Four (4) different percentages of levels POC as aggregate replacement were prepared. There are 0 %, 5 %, 10 % and 15 % of POC from total weight of aggregate used. In this study, the specimens were heated in the furnace at 200°C, 400°C, 600°C and 800°C for one (1) hour. Then, the strength properties of specimens in terms of compressive strength at 7, 28 and 60 days were investigated. The mode failure of specimens with and without POC after subjected to high temperatures were observed and studied.